2015
DOI: 10.1016/j.janxdis.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotionality and disconstraint influence PTSD symptom course via exposure to new major adverse life events

Abstract: Identifying the factors that influence stability and change in chronic posttraumatic stress disorder (PTSD) is important for improving clinical outcomes. Using a cross-lagged design, we analyzed the reciprocal effects of personality and PTSD symptoms over time and their effects on stress exposure in a sample of 222 trauma-exposed veterans (ages 23 -68; 90.5% male). Personality functioning and PTSD were measured approximately 4 years apart, and self-reported exposure to major adverse life events during the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
8
30
0
1
Order By: Relevance
“…Based on the types of stressful events endorsed during the follow‐up period, our findings may reflect the tendency for individuals who engage in RSDB to select into dangerous environments that put them at risk for physical injury (e.g., car accidents, assaultive events) and/or associate with others who place themselves at risk for premature death or life‐threatening injury (e.g., aggressive or substance‐abusing individuals). This finding converges with our previous study (Sadeh et al., ), which found that the personality traits of negative emotionality and disconstraint perpetuate PTSD symptoms over time, in part, by increasing exposure to new adverse events. However, a key difference between this study and Sadeh et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on the types of stressful events endorsed during the follow‐up period, our findings may reflect the tendency for individuals who engage in RSDB to select into dangerous environments that put them at risk for physical injury (e.g., car accidents, assaultive events) and/or associate with others who place themselves at risk for premature death or life‐threatening injury (e.g., aggressive or substance‐abusing individuals). This finding converges with our previous study (Sadeh et al., ), which found that the personality traits of negative emotionality and disconstraint perpetuate PTSD symptoms over time, in part, by increasing exposure to new adverse events. However, a key difference between this study and Sadeh et al.…”
Section: Discussionsupporting
confidence: 92%
“…Between T1 and T2, 82.0% of the sample reported at least one new adverse event, and the mean number reported was 1.86 ( SD = 1.96, range = 0 to 9). The most commonly reported adverse events were sudden death of a friend or loved one (36.5%), threatened with or completed physical assault (24.3%), motor vehicle accident (22.3%), life‐threatening or disabling event to a loved one (20.3%), life‐threatening illness (19.6%), and witnessing a severe accident (8.1%; these data overlap with the results found in Sadeh et al., ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…A third possibility is that genetic liability for behavioral disinhibition increases the likelihood that an individual will be exposed to high-risk environments where they will be exposed to traumatic events (i.e., indicative of a gene-environment correlation), which in turn potentiates externalizing psychopathology. Such a model is consistent with research showing that impulsivity leads to greater trauma and life stress exposure prospectively (e.g., Sadeh, Miller, Wolf, & Harkness, 2015). However, a relationship between the polygenic risk score and lifetime trauma exposure was not evident in our samples, suggesting that gene-environment correlation is unlikely.…”
Section: Discussionsupporting
confidence: 89%
“…It was unclear if NEGE would also be associated with combat exposure as this prospective relation has not been extensively studied. It was also unclear if baseline internalizing and externalizing symptoms would be related to combat exposure as findings in this area have been inconsistent (Breslau et al , 1995, Sadeh et al , 2015)…”
mentioning
confidence: 99%